Epigenetic Mechanisms Underlying Sex Differences in Neurodegenerative Diseases - Andrea Stoccoro (Biology)
Neurodegenerative diseases are characterized by profound differences between females and males in terms of incidence, clinical presentation, and disease progression. Furthermore, there is evidence suggesting that differences in sensitivity to medical treatments may exist between the two sexes. Although the role of sex hormones and sex chromosomes in driving differential susceptibility to these diseases is well-established, the molecular alterations underlying these differences remain poorly understood. Epigenetic mechanisms, including DNA methylation, histone tail modifications, and the activity of non-coding RNAs, are strongly implicated in the pathogenesis of neurodegenerative diseases. While it is known that epigenetic mechanisms play a crucial role in sexual differentiation and that distinct epigenetic patterns characterize females and males, sex-specific epigenetic patterns have been largely overlooked in studies aiming to identify epigenetic alterations associated with neurodegenerative diseases. This review aims to provide an overview of sex differences in epigenetic mechanisms, the role of sex-specific epigenetic processes in the central nervous system, and the main evidence of sex-specific epigenetic alterations in three neurodegenerative diseases, including Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis. Understanding the sex-related differences of these diseases is essential for developing personalized treatments and interventions that account for the unique epigenetic landscapes of each sex.